SUBGRUP -NORMAL DAN SUBRING -MAX - Kristi Utomo Kristi Utomo (Jurnal Matematika, 2016)
ABSTRACT. For any group , subgroup  of  is called -normal subgroup if there exist a normal subgroup  of  such that  and  where  is maximal normal subgroup of  which is contained in . On the other side, for each ring , subring  of  is called -max subring if there exist an ideal  of  such that  and  where  is maximal ideal of  which is contained in . Subgroup normal  of  is -normal subgroup if and only if  is maximal normal subgroup and ideal  of  is -max subring if and only if  is maximal ideal. Every group and ring is -normal subgroup and -max subring of itself.